BEYOND THE CAMPAIGN: MANAGING MARKETING AS A CONTINUOUS CUSTOMER CONVERSATION - Wan Repli; Lukmanul Hakim; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In the digital era, the traditional campaign-based marketing model is increasingly misaligned with the perpetual, always-on nature of consumer engagement. This research addresses the strategic shift required to move from episodic campaigns towards managing marketing as a continuous, data-driven conversation with the customer. The objective was to identify the operational and cultural frameworks that enable organizations to sustain meaningful dialogue across the entire customer lifecycle. A qualitative methodology was employed, utilizing semi-structured interviews with twenty-five senior marketing leaders from digitally mature organizations and a thematic analysis of internal strategy documents. The results reveal that successful transition hinges on three pillars: an agile, content-led engagement strategy; an integrated technology stack enabling real-time interaction management; and an organizational culture that prioritizes customer listening and iterative learning over rigid campaign calendars. The discussion emphasizes that this approach fosters greater brand relevance, improves customer lifetime value, and drives more efficient resource allocation. In conclusion, managing marketing as a continuous conversation is not merely a tactical change but a fundamental strategic reorientation, demanding new capabilities, metrics, and leadership mindsets to thrive in a perpetually connected marketplace.